The implementation of Usrah in the International Islamic University Malaysia and its contributions to holistic student development - Nik Abdullah, Nik Md. Saiful Azizi; Dollah, Nafi@Hanafi; Awang Marusin, Awang Abdul Muizz (Penerbit USIM, Universiti Sains Islam Malaysia (USIM), 2018)
This paper aims to explain the implementation of Usrah in residential colleges (Mahallat) of the International Islamic University Malaysia (IIUM) as well as to analyse its relationship with human development and its contributions towards holistic student development. As a qualitative study, a case study was conducted under the leadership of 215 leaders, 2,004 participants joined Usrah Mahallah in Semester 1, Academic Year 2017/2018. In addition to the fact that 87.47 percent of participants recorded excellent participation in such semester, findings shown that participants accepted Usrah Mahallah as a part of their life as IIUM students. Three factors contributed to such happiness: modern and friendly approaches applied by leaders, organisation of attractive Usrah Mahallah activities, and conducive environment of Usrah Mahallah inculcated jointly by leaders and participants. Consequent to those findings, Usrah Mahallah is not only regarded as a progressive product of Islamisation in IIUM, but also considered capable in providing students with supplementary social, spiritual and intellectual values which will help IIUM in establishing better community with better social and spiritual state in the future.